Penentuan Sistem Pengadaan Bahan Baku Utama Berbasis Kontrak pada Perusahaan Roti dan Kue-Kue ANDALAS - Irma Felicia; Carles Sitompul; Paulina Kus Ariningsih (Universitas Katolik Parahyangan, 2021)
Micro, small and medium enterprises (MSME) are striving to maximize profits through cost’s reduction while maintaining their product qualities and their customer’s satisfaction. ANDALAS is an MSME producing cakes and breads that intuitively purchase its raw material which results in a relatively high purchase cost. We propose a contract-based system using a linear programming approach to manage the purchasing activities of main ingredients. A mathematical model is proposed supporting the purchasing decisions which includes constraints such as: minimum purchase, safety stock, warehouse capacity, and demand’s requirements. The resulting model provides an improvement of 6,30% reduction in purchase costs. The improvement for each ingredient ranges from 4% to 16% where Eggs, Flour, Maizena, Margarine, Butter and Sugar are contractually ordered from one main supplier.